The Relationship between Fear of Missing Out (FOMO) and Consumptive Behavior among High School Students in West Palu District - Mastura, Ade Avriliani MY.; Fitriani, Dian; Hasan, Hasan; Nurwahyuni, Nurwahyuni (Indonesian Journal of Counseling and Development, 2025)
The widespread use of digital platforms among secondary school students has led to the emergence of Fear of Missing Out (FOMO), a social anxiety characterised by feelings of exclusion from enjoyable activities experienced by others. Social media features, such as daily stories and live streams on platforms like Instagram and YouTube, encourage students to follow trends. High levels of FOMO are associated with consumerist behaviour, where students purchase items they do not truly need simply to align with lifestyle trends or popular phenomena. This study aims to determine the correlation between FOMO and consumptive behavior among high school students in West Palu District. A total of 300 students were selected using purposive sampling, and the data were analyzed descriptively and inferentially through classical assumption tests (normality and linearity) and product moment correlation. The results showed that 68.66% of students experienced high FOMO, and 52.33% exhibited high consumptive behavior. Pearson's correlation analysis yielded r = 0.767 with p < 0.05, which is greater than the table r of 0.113, thus rejecting the null hypothesis and accepting the alternative hypothesis. These findings serve as a reference for counselors through classical guidance to explain the influence of social media algorithms and influencers, as well as through group counseling services for students with excessive impulsive tendencies. These services can help students shift from FOMO (Fear of Missing Out) to JOMO (Joy of Missing Out) in order to be wiser in their use of social media and consumption patterns.